Revisions of Australian ground-hunting spiders: IV. The spider subfamily Diaprograptinae subfam. nov. (Araneomorphae: Miturgidae) - Raven, Robert J. (Zootaxa, 2009)
The newly recognised Diaprograptinae includes the Australian Diaprograpta Simon, 1909, Eupograpta gen. nov., Mituliodon Raven & Stumkat, 2003, Mitzoruga gen. nov., Nuliodon gen. nov., and the New Zealand Zealoctenus Forster & Wilton, 1973. All genera are unique in the Miturgidae s. strict. in the possession of claw tufts, and more equivocally, in the apical segment of the posterior lateral spinnerets, which in Diaprograptinae is not as strongly elongated as in Miturga. Diaprograpta includes the type species, D. striola Simon, 1909 from Western Australia, D. hirsti sp. nov. from South Australia, D. alfredgodfreyi sp. nov. from Victoria, D. peterandrewsi sp. nov. from western Queensland and D. abrahamsae sp. nov. from southeast Queensland. Eupograpta includes E. kottae sp. nov., sympatric with Diaprograpta striola and E. anhat sp. nov., from western Queensland. Mitzoruga gen. nov. is described to accommodate Uliodon marmoreus (Hogg, 1896), M. insularis sp. nov., and M. elapines sp. nov., from xeric regions of Australia. The genus presents a character combination which challenges the boundary between the Miturgidae Simon, 1886 and Zoridae F. O. P.-Cambridge, 1893. Nuliodon gen. nov. includes only N. fishburni sp. nov. from eastern Australia.